Topical cyclosporine for severe dry eye disease in liver-transplanted Portuguese patients with familial amyloidotic polyneuropathy (ATTRV30M) - Beirão, J.M. (2014)
PURPOSE. Evaluation of the use of topical cyclosporine eyedrops in the treatment of severe dry eye disease in liver transplanted patients with familial amyloidotic polyneuropathy (FAP) unresponsive to therapy with artificial tears and lacrimal plugs. METHODS: A prospective clinical study of 5 patients (10 eyes) admitted to the Ophthalmology Department of the Centro Hospitalar do Porto with severe dry eye disease refractory to artificial tears and lacrimal plug treatments. Evaluation of the patients included best-corrected visual acuity, corneal punctuate fluorescein staining, tear break-up time, Schirmer test without anesthesia, and Ocular Surface Disease Index. Patients were observed at time 0, and at 3, 7, and 11 months. RESULTS: Treatment with topical cyclosporine improved all studied parameters from baseline, and in all the patients (p<0.001). The safety profile was excellent, without topical or systemic adverse events. CONCLUSIONS: Topical cyclosporine was beneficial in the treatment of severe dry eye disease in liver transplanted patients with FAP.